Academics’ link with the university and the relevance of the spirituality and dentistry project during the covid-19 pandemic - Ramson, Kamila Pagel; Fonseca, Laura da Silva; Coutinho, Rafaela Dias; Mello, André Luiz Rodrigues; Pinto, Larissa Moreira; de Sousa, Ezilmara Leonor Rolim (Seven Editora, 2023)
The teaching project "Spirituality and Dentistry: A more humanized care", proposes to the students a broad and more humanized view of the patient as an integral being, as well as demonstrating the role of spirituality in the health-disease process. With the COVID-19 pandemic, the project needed to reformulate its methodology in the face of the reality of remote teaching and thus maintain the link between academics and the university. Thus, this study aimed to verify - through the application of an online questionnaire - whether the methodology employed was satisfactory for the students and whether it had a positive impact on their education and on their bond with the university. The result of the research showed that most students consider that participating in the project activities influenced them in a positive way, both in the personal sphere and in the student/patient relationship at the university. In addition, most students expressed the desire for these teaching activities to continue to take place. It is concluded that the project participants perceived positive differences both in the personal sphere and in the student/patient relationship during the pandemic, because they were involved in the Spirituality and Dentistry teaching project. DOI:https://doi.org/10.56238/ptoketheeducati-060